The ersatz elevator a series of unfortunate events - Snicket, Lemony (HarperCollins New York, 2001)
The woeful saga of the Baudelaire orphans continues as evil Count Olaf discovers their whereabouts at Esmé Squalor's seventy-one bedroom penthouse and concocts a new plan for stealing their family fortune